Analisis Kebutuhan Pengembangan E-LKPD Bernuansa Emotional Spiritual Quotient (ESQ) pada Materi Virus untuk Peserta Didik Fase E SMA/MA - Susanto, Edi; Lufri, Lufri (LP2M IAIN Ambon, 2025)
This study aims to analyze the need for E-LKPD with an Emotional Spiritual Quotient (ESQ) focus as a learning aid in biology education, particularly for virus-related material at the phase E level of senior high school/madrasah aliyah. The research method used is descriptive with a quantitative and qualitative approach. Data was collected through interviews with a biology teacher and the distribution of observation sheets to 99 students from classes X E1, X E2, and X E3 at SMA N 2 Lubuk Basung. The results of this study, based on the teacher's interview, indicate that teachers use media such as PowerPoint and educational videos from YouTube in the learning process, but have never developed E-LKPD with an Emotional Spiritual Quotient (ESQ) focus in the learning process. From these findings, it can be concluded that there is a significant need to develop E-LKPD with an Emotional Spiritual Quotient (ESQ) focus on virus related material.